Diversity of soil spiders in land use and management systems in santa catarina, Brazil Diversidade de aranhas edáficas em sistemas de uso e manejo do solo em santa catarina, brasil - da Rosa M.G.* (2019)
© 2019, Universidade Estadual de Campinas UNICAMP. All rights reserved.The ability of spiders to spread over contiguous areas (Arachnida: Araneae) is directly related to soil management conditions. The objective of this work was to study the effect of land use system (LUS) on the abundance and diversity of soil spider families and their relationship with soil physical and chemical properties. The evaluated LUS were: native forest, eucalyptus reforestation, pasture, crop-livestock integration, and no-tillage crop. Samples were collected in three municipalities of Southern Plateau of Santa Catarina, considered as true replicates, during winter and summer. A total of 270 samples was taken in each area and season. The sampling points were arranged in a grid of 3 × 3 m, spaced by 30 m. We evaluated soil physical, chemical, and microbiological attributes and the abundance and diversity of spider families, collected by soil monolith and soil traps. A total of 448 spiders were captured, 152 in winter and 296 in summer, distributed in 24 families and 52 species/morphospecies. There was a seasonality effect related to the land use systems and the highest Shannon-Wiener diversity index was recorded in the native forest in both sampling periods. Most families of spiders have a direct dependence on soil physical and chemical properties, such as microporosity, exchangeable aluminum, calcium, magnesium, and potassium during the winter. Organic matter, nitrogen, pH in water, weighted average diameter, soil density, and microbial biomass carbon exhibited dependence during the summer. Vegetation type and soil management are the factors that seem to affect most the occurrence of spiders. The families Theridiidae and Nemesiidae are dependent on sites with low human intervention.